Establishing a Core Outcome Measure for Life Participation: A Standardized Outcomes in Nephrology – Kidney Transplantation (SONG-Tx) Consensus Workshop Report. (July 2018) - Ju, Angela; Josephson, Michelle A; Jowsey-Gregoire, Sheila; Tan, Jane; Taylor, Quinetta; Flower, Kevin; Dobbels, Fabienne; Caskey, Fergus; Jha, Vivekanand; Locke, Jayme; Knoll, Greg; Ahn, Curie; et al.
Abstract : Background: Life participation is a critically important outcome for kidney transplant recipients but it is inconsistently and infrequently measured in trials. We convened a consensus workshop on establishing a core outcome measure for life participation for use in all trials in kidney transplantation. Methods: Twenty-five (43%) kidney transplant recipients/caregivers and 33 (57%) health professionals from eight countries participated. Transcripts were analyzed thematically. Results: Four themes were identified. Returning to normality illustrated the patients' desires to fulfil their given role and re-establish a normal lifestyle. Recognizing the diverse meaning of 'life' explicitly acknowledged life participation as a subjective outcome that may refer to different activities for different patients. Capturing fluctuations in issues post-transplant recognized the long-term impact of transplantation and emphasized the need to consider time since receiving the transplant. Having a scientifically rigorous, feasible and meaningful measure would facilitate the consistent and frequent assessment of life participation in trials. Conclusions: A simple and inexpensive core outcome measure for life participation will allow this important outcome to be consistently and meaningfully assessed in trials in kidney transplantation to inform decision-making and care of patients